High fatigue life alloy steel bar for oilfield drilling tools and method for manufacturing the same

CN122979737APending Publication Date: 2026-10-27ZHANGJIAGANG SHENGGANG MACHINERY MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611470559.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

另一方面,裂纹一旦形成,氢的富集会降低裂纹尖端区域的韧性,减少裂纹扩展阻力,使裂纹扩展速率加快,这种裂纹的快速扩展直接导致疲劳寿命大幅缩短

Benefits of technology

[0067]与现有技术相比,本发明的有益效果为:(1)通过引入钯,在钢基体中形成高效的氢陷阱,降低扩散氢的浓度和迁移速率,与传统技术相比,钯能直接捕获扩散性氢原子,并阻止氢的富集和裂纹的萌生扩展;(2)通过引入镧,利用其与钢中氧、硫的高亲和性生成La基氧化物/硫化物夹杂,将尖锐的夹杂变为球状或弥散分布的小尺寸夹杂,减少了疲劳裂纹的形核源,还能吸附扩散氢,进一步降低氢的危害。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application belongs to the technical field of alloy steel bars, and provides an alloy steel bar with high fatigue life for oilfield drilling tools and a preparation method thereof; first, the steel material is put into an electric arc furnace and heated to high temperature, and oxygen is blown through an oxygen lance, lime and fluorite are added to form a foamed slag, so that preliminary refining of decarburization, dephosphorization and desulfurization is realized; under vacuum and argon protection environment, a palladium wire and a lanthanum wire are sequentially fed, and soft argon blowing is used to realize component homogenization, and finally a uniform and dense continuous casting is obtained by pouring; the continuous casting is subjected to high-temperature forging to refine grains, rolled to form a fibrous structure, and further optimized through normalizing and tempering heat treatment to form a uniform and fine tempered troostite or pearlite matrix; the palladium forms hydrogen traps by capturing diffused hydrogen, and the lanthanum reduces crack sources by inclusion modification, and the synergistic effect of the two reduces the hydrogen embrittlement sensitivity of the steel material and improves the fatigue life of the alloy bar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of alloy steel bars, and relates to high fatigue life alloy steel bars for oilfield drilling tools and their preparation methods. Background Technology

[0002] Hydrogen embrittlement is a typical phenomenon in which steel fails due to the intrusion of hydrogen atoms into the material in a hydrogen-containing environment, significantly impacting its fatigue life. Hydrogen embrittlement is usually related to the penetration of external hydrogen and hydrogen introduced during the manufacturing process. External hydrogen primarily originates from corrosive media and high-pressure hydrogen environments. For example, in oilfield drilling tools, chemical equipment, and marine engineering, steel is exposed to acidic or hydrogen-containing gas environments for extended periods, allowing hydrogen atoms to penetrate the steel surface and diffuse into the interior. The negative impact of hydrogen embrittlement on the fatigue life of steel manifests in two main ways. First, hydrogen atoms tend to accumulate at defect sites, making crack nucleation more likely under cyclic loading and significantly shortening the crack initiation cycle. Second, once a crack forms, hydrogen enrichment reduces the toughness of the crack tip region, decreasing crack propagation resistance and accelerating the crack propagation rate. This rapid crack propagation directly leads to a substantial reduction in fatigue life. Summary of the Invention

[0003] To address the shortcomings of existing technologies, the present invention aims to provide high fatigue life alloy steel bars for oilfield drilling tools and their preparation method. In electric arc furnace smelting, oxygen blowing with an oxygen lance and the addition of lime and fluorite to form foam slag effectively remove impurities from the molten steel. The heat exchange and desulfurization process is optimized by controlling the slag layer thickness. Subsequently, the molten steel is transferred to a vacuum induction furnace, where palladium and lanthanum wires are sequentially fed under extremely low vacuum and argon protection conditions. Palladium traps diffused hydrogen through a hydrogen trapping mechanism, while lanthanum significantly improves the morphology and distribution of inclusions through inclusion modification. Combined with electromagnetic stirring and light reduction processes, the uniformity of the microstructure of the finished continuous castings is ensured. Subsequent forging, rolling, normalizing, and tempering heat treatment processes meet the needs of actual production.

[0004] To achieve this objective, the present invention adopts the following technical solution:

[0005] In a first aspect, the present invention provides a method for preparing high fatigue life alloy steel bars for oilfield drilling tools, the method comprising:

[0006] S1. Steel is put into an electric arc furnace and oxygen is blown in with an oxygen lance. Lime and fluorite are added to form foam slag to obtain molten steel. The molten steel is transferred to a vacuum induction melting furnace, vacuum is drawn and maintained, and Pd wire and La wire are fed in sequence under argon atmosphere. After feeding the wire, argon is blown in soft air, the crystallizer is turned on with electromagnetic stirring, and a light pressing process is implemented to cast the continuous casting.

[0007] S2, the continuous casting is forged, rolled, normalized and tempered in sequence to obtain high fatigue life alloy steel bars for oilfield drilling tools.

[0008] Specifically, it includes:

[0009] S1. Steel is fed into an electric arc furnace, the furnace temperature is kept at the first temperature, and oxygen is blown in with an oxygen lance. Lime and fluorite are added to form foam slag. The slag layer thickness is controlled at 10-15cm to obtain molten steel. The molten steel is transferred to a vacuum induction melting furnace, vacuum is drawn and maintained, and Pd wire and La wire are fed in sequence under argon atmosphere. After wire feeding, argon is gently blown in, the crystallizer is turned on with electromagnetic stirring, and a light pressing process is implemented to cast the continuous casting.

[0010] S2, the continuous casting is forged, rolled, normalized and tempered in sequence to obtain high fatigue life alloy steel bars for oilfield drilling tools.

[0011] The steel is placed in an electric arc furnace, where the temperature rises rapidly through the electric arc, reaching the high-temperature range required for melting. During this process, the introduction of an oxygen lance not only provides the necessary oxidant but also achieves preliminary refining—decarburization, dephosphorization, and desulfurization—through oxidation reactions with impurities such as carbon, phosphorus, and sulfur in the molten steel. The addition of lime and fluorite further enhances the slag-metal reaction during smelting. Lime, through its reaction with the oxidation products of sulfur and phosphorus, forms a high-melting-point, viscous composite slag phase, thereby fixing impurities and separating them from the molten steel. The addition of fluorite reduces slag viscosity and improves the kinetics of the slag-metal interface reaction. These reactions form a uniform foamy slag layer covering the surface of the molten steel. This layer not only isolates the molten steel from direct contact with air, reducing secondary oxidation, but also effectively captures inclusions that have not yet floated to the surface. After the preliminary smelting in the electric arc furnace, the molten steel is transferred to a vacuum induction melting furnace for further refining operations to improve its purity and compositional uniformity. During this stage, the evacuation rate of dissolved gases in the molten steel is significantly increased by vacuuming. In addition, the vacuum environment reduces the partial pressure of oxygen, which, combined with the reaction of the reducing agent in the molten steel, further reduces the residual oxygen content, ensuring that the subsequently added palladium and lanthanum can react with the molten steel in an efficient and stable manner.

[0012] In the low-oxygen environment of vacuum induction melting, palladium and lanthanum are sequentially added to molten steel via a wire-feeding process. The addition of palladium wire is based on its unique role in forming "hydrogen traps" in the steel matrix. Palladium atoms, by dissolving in the crystal lattice of the steel matrix, provide efficient pinning sites in the interstitial spaces, trapping diffusive hydrogen atoms and reducing their migration ability. This lowers the concentration gradient of diffusive hydrogen in the steel, thereby inhibiting hydrogen accumulation in high-stress areas (such as crack tips) and reducing the risk of hydrogen-induced crack initiation. The subsequently fed lanthanum wire mainly reacts with residual oxygen and sulfur in the molten steel to generate rare earth oxide and sulfide inclusions. These La-based inclusions exhibit a spherical or finely dispersed distribution, significantly optimizing the inclusion morphology in the molten steel and reducing the risk of sharp inclusions inducing cracks under fatigue loads. Furthermore, due to their high surface energy, La-based inclusions can further adsorb diffusive hydrogen, thus synergistically enhancing the steel's resistance to hydrogen embrittlement. After wire feeding, the molten steel is stirred using soft-blown argon gas to enhance the uniformity of palladium and lanthanum distribution. The fluidity and stirring effect of argon gas help improve the chemical homogeneity of the molten steel and promote the flotation and separation of inclusions, further enhancing the purity of the steel. Once the molten steel is prepared, it is transferred to a crystallizer for casting. During this process, electromagnetic stirring in the crystallizer drives the flow of the molten steel through electromagnetic force, suppressing macroscopic segregation and liquid-phase separation during solidification. Simultaneously, a light reduction process is implemented, applying slight compression deformation to the billet to reduce central shrinkage cavities and improve the internal density of the billet, ensuring the compositional homogeneity and microstructure of the final continuous casting, providing a high-quality billet base for subsequent forging and heat treatment.

[0013] In the initial forging stage, the steel billet is heated to a high-temperature range where austenite is stable, at which point the ferrite in the steel completely transforms into austenite. Due to its high plasticity and low flow stress, austenite can be fully deformed under forging stress. During deformation, the coarse grains in the as-cast state are broken up, and casting defects such as internal porosity and segregation are densified through plastic deformation. Simultaneously, the numerous dislocations and grain boundaries generated during forging provide a favorable microstructural basis for subsequent heat treatment. In the final forging stage, a lower temperature is controlled to avoid unnecessary grain growth, while ensuring uniform stress distribution within the material and preventing stress concentration due to uneven cooling. The rolling stage further refines the steel's microstructure and stabilizes the internal structure with relatively small deformation. During rolling, austenite grains are elongated along the rolling direction, forming an excellent fibrous structure, which helps improve the steel's fatigue resistance. Simultaneously, the multiple deformation passes during rolling significantly increase the number of grain boundaries, which, acting as hydrogen diffusion barriers, further prevent long-distance hydrogen migration and accumulation in the steel. In addition, during the rolling process, inclusions are elongated and dispersed to a certain extent. This refinement and homogenization effect reduces the induction of fatigue cracks by inclusions.

[0014] During the normalizing heating stage, the steel is heated to the austenite stability range, at which point the original ferrite and pearlite structures are completely transformed into a uniform austenite structure. Subsequently, by controlling the cooling rate, the austenite decomposes, forming fine ferrite and pearlite structures. The microstructure refinement after normalizing significantly improves the toughness and strength of the steel. Lanthanum-based inclusions maintain a stable dispersed distribution during normalizing due to their high melting point, and further refine the surrounding matrix structure through the interface effect, reducing the probability of fatigue crack initiation. The tempering process, by holding at an appropriate temperature and slowly cooling, releases the internal stress of the steel and further optimizes the microstructure. During tempering, the residual ferrite and pearlite structures from normalizing undergo stress relaxation, while more stable carbide phases precipitate. Palladium, during the tempering stage, effectively pins hydrogen atoms through its high affinity for hydrogen, inhibiting their migration in the matrix. The microstructure after tempering is mainly composed of tempered troostite or fine pearlite, the grain boundaries are further stabilized, the uniformity of the microstructure is significantly enhanced, and the fatigue resistance of the steel is improved.

[0015] As a preferred technical solution of the present invention, in S1, the first temperature is 1600-1650℃, for example, it can be 1600℃, 1605℃, 1610℃, 1615℃, 1620℃, 1625℃, 1630℃, 1635℃, 1640℃, 1645℃ or 1650℃, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0016] In some optional instances, the oxygen lance blowing time is 20-30 min, for example, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0017] In some optional instances, the oxygen lance blows oxygen at a flow rate of 300-400 Nm³. 3 / h, for example, could be 300 Nm 3 / h、310 Nm 3 / h, 320 Nm 3 / h、330 Nm 3 / h, 340 Nm 3 / h, 350 Nm 3 / h, 360 Nm 3 / h、370 Nm 3 / h, 380 Nm 3 / h, 390 Nm 3 / h or 400 Nm3 / h, but not limited to the listed values; other unlisted values ​​within this range also apply.

[0018] In some optional instances, the thickness of the slag layer is controlled to be 10-15 cm, for example, it can be 10.0 cm, 10.5 cm, 11.0 cm, 11.5 cm, 12.0 cm, 12.5 cm, 13.0 cm, 13.5 cm, 14.0 cm, 14.5 cm or 15.0 cm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0019] In some optional instances, the vacuum degree of the vacuum induction melting furnace is ≤0.08 Pa.

[0020] In some optional instances, the feeding speed of the Pd wire is 10-12 m / min, for example, it can be 10.0 m / min, 10.2 m / min, 10.4 m / min, 10.6 m / min, 10.8 m / min, 11.0 m / min, 11.2 m / min, 11.4 m / min, 11.6 m / min, 11.8 m / min or 12.0 m / min, and the diameter of the Pd wire is 1.0-1.2 mm, for example, it can be 1.00 mm, 1.02 mm, 1.04 mm, 1.06 mm, 1.08 mm, 1.10 mm, 1.12 mm, 1.14 mm, 1.16 mm, 1.18 mm or 1.20 mm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0021] In some optional instances, the feeding speed of the La filament is 10-12 m / min, for example, it can be 10.0 m / min, 10.2 m / min, 10.4 m / min, 10.6 m / min, 10.8 m / min, 11.0 m / min, 11.2 m / min, 11.4 m / min, 11.6 m / min, 11.8 m / min or 12.0 m / min, and the diameter of the La filament is 1.0-1.2 mm, for example, it can be 1.00 mm, 1.02 mm, 1.04 mm, 1.06 mm, 1.08 mm, 1.10 mm, 1.12 mm, 1.14 mm, 1.16 mm, 1.18 mm or 1.20 mm, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0022] In some optional instances, the soft blowing time of argon is ≥15 min, and the argon flow rate is 13-15 L / min, for example, it can be 13.0 L / min, 13.2 L / min, 13.4 L / min, 13.6 L / min, 13.8 L / min, 14.0 L / min, 14.2 L / min, 14.4 L / min, 14.6 L / min, 14.8 L / min or 15.0 L / min, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0023] In some alternative instances, the current of the electromagnetic stirring of the crystallizer is 280-300A, for example, 280A, 282A, 284A, 286A, 288A, 290A, 292A, 294A, 296A, 298A or 300A, with a frequency of 2Hz, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0024] In some optional instances, the total reduction of the light reduction process is 4 mm / m.

[0025] In some optional instances, the pouring temperature is 1530-1560°C, for example, it can be 1530°C, 1533°C, 1536°C, 1539°C, 1542°C, 1545°C, 1548°C, 1551°C, 1554°C, 1557°C or 1560°C, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0026] As a preferred technical solution of the present invention, in S2, the initial forging temperature is 1150-1200℃, for example, it can be 1150℃, 1155℃, 1160℃, 1165℃, 1170℃, 1175℃, 1180℃, 1185℃, 1190℃, 1195℃ or 1200℃, and the final forging temperature is 850-900℃, for example, it can be 850℃, 855℃, 860℃, 865℃, 870℃, 875℃, 880℃, 885℃, 890℃, 895℃ or 900℃, the total deformation is ≥4 times, and the single compression ratio is ≤30%, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0027] In some optional examples, the initial rolling temperature is 1100-1150℃, for example, 1100℃, 1105℃, 1110℃, 1115℃, 1120℃, 1125℃, 1130℃, 1135℃, 1140℃, 1145℃, or 1150℃, and the final rolling temperature is 800-850℃, for example, 800℃, 805℃, 810℃, 815℃, 820℃, 825℃, or 830℃. The rolling temperature is 0℃, 835℃, 840℃, 845℃ or 850℃, with a reduction of ≤20% per rolling pass. The rolling specification is Φ80-100mm, such as 80mm, 82mm, 84mm, 86mm, 88mm, 90mm, 92mm, 94mm, 96mm, 98mm or 100mm. After rolling, the material is buried in sand for cooling, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0028] In some optional examples, the normalizing temperature is 880-900℃, for example, it can be 880℃, 882℃, 884℃, 886℃, 888℃, 890℃, 892℃, 894℃, 896℃, 898℃, or 900℃, and the heating rate is 10-15℃ / min, for example, it can be 10.0℃ / min, 10.5℃ / min, 11.0℃ / min, 11.5℃ / min, 12.0℃ / min, 12.5℃ / min, or 13.0℃. The temperature can be 13.5℃ / min, 14.0℃ / min, 14.5℃ / min, or 15.0℃ / min, with a holding time of 90-100 min, such as 90 min, 91 min, 92 min, 93 min, 94 min, 95 min, 96 min, 97 min, 98 min, 99 min, or 100 min. After removing from the oven, the temperature should be air-cooled to room temperature. However, the temperature is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0029] In some optional examples, the tempering temperature is 540-560°C, for example, 540°C, 542°C, 544°C, 546°C, 548°C, 550°C, 552°C, 554°C, 556°C, 558°C, or 560°C, with a heating rate of 10-15°C / min, for example, 10.0°C / min, 10.5°C / min, 11.0°C / min, 11.5°C / min, 12.0°C / min, 12.5°C / min, etc. The furnace temperature is set at 13.0℃ / min, 13.5℃ / min, 14.0℃ / min, 14.5℃ / min, or 15.0℃ / min, with a holding time of 2-3 hours, such as 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours, or 3.0 hours. After removal from the furnace, the furnace is air-cooled to room temperature. However, the furnace temperature is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0030] In a second aspect, the present invention provides high fatigue life alloy steel bars for oilfield drilling tools prepared by the preparation method described in the first aspect. The chemical composition, by mass percentage, is as follows: C: 0.20–0.75%, Si: 0.10–0.60%, Mn: 0.10–0.85%, Cr: 0.80–1.90%, Pd: 0.01–0.02%, La: 0.005–0.015%, S: ≤0.002%, P≤0.008%, Nb: 0.01–0.08%, Mo: 0.10–0.80%, V: 0.02–0.20%, W: 0.10–1.00%, Al≤0.05%, Ca: 0.002–0.006%, Ti≤0.003%, O≤0.0010%, As≤0.04%, Sn≤0.03%, Sb≤0.005%, Pb≤0.002%, with the balance being Fe and unavoidable impurities.

[0031] The chemical composition design of the steel for oilfield drilling tools in this invention is based on the following:

[0032] 1) Determination of C content

[0033] Carbon (C) is an essential element for ensuring wear resistance. In steel, carbon increases hardness and strength by enhancing martensitic transformation, thereby improving wear resistance. However, a C content exceeding 0.75% increases susceptibility to cracking during precision forging and heat treatment. This invention controls its content to 0.20–0.75%.

[0034] 2) Determination of Si content

[0035] Si is a deoxidizer in the steelmaking process, and it improves the hardness, strength, elastic limit, and yield strength ratio of steel through solid solution strengthening. It reduces the diffusion rate of carbon in ferrite, making it less likely for carbides precipitated during tempering to aggregate, thus improving the steel's resistance to tempering softening. In addition, Si reduces oxidation during frictional heating and increases the cold work hardening rate of steel, thereby improving the material's wear resistance. However, excessively high Si content will reduce the toughness of the steel. This invention controls the Si content to be 0.10–0.60%.

[0036] 3) Determination of Mn content

[0037] Mn, as a deoxidizing element in the steelmaking process, is an effective strengthening element for steel, playing a solid solution strengthening role to compensate for the strength loss caused by the reduction of carbon content in the steel. Furthermore, Mn can improve the hardenability and hot working properties of steel. Mn can eliminate the influence of sulfur: in steelmaking, Mn can combine with sulfur to form high-melting-point MnS, thereby weakening and eliminating the adverse effects of sulfur. An Mn content higher than 0.85% will significantly reduce the toughness of the steel. In this invention, the Mn content is controlled between 0.10% and 0.85%.

[0038] 4) Determination of Cr content

[0039] Cr is a carbide-forming element that improves the hardenability, wear resistance, and corrosion resistance of steel. In steel, some Cr replaces iron to form alloyed cementite, improving the tempering stability of the steel; others dissolve into ferrite, resulting in solid solution strengthening and increasing the strength and hardness of the ferrite. However, excessively high Cr content can lead to the formation of large carbides by combining with carbon in the steel. These large carbides reduce the torsional fatigue life of the steel. Based on the above analysis, the Cr content range in this invention is determined to be 0.80%–1.90%.

[0040] 5) Determination of Nb content

[0041] Nitrogen (Nb) is both a strong ferrite-forming element and a strong carbonitride-forming element, and it readily forms metallic compounds when heated for extended periods. To control costs and achieve the desired results, the Nb content in this invention is determined to be in the range of 0.01% to 0.08%.

[0042] 6) Determination of Mo content

[0043] Molybdenum refines the grain size of steel, improves hardenability and hot strength, and maintains sufficient strength and creep resistance at high temperatures. Adding molybdenum to steel improves mechanical properties and can also suppress brittleness caused by tempering in alloy steels. However, molybdenum is a ferrite-forming element; when the molybdenum content is high, ferrite δ phase or other brittle phases are more likely to form, reducing toughness. In this invention, the Mo content is defined as ranging from 0.10% to 0.80%.

[0044] 7) Determination of V content

[0045] Vanadium carbonitrides (such as VC and VN) pin grain boundaries during high-temperature rolling, controlling the austenite grain size to 10-20 μm (30-50 μm without addition). This grain refinement improves steel toughness (increasing impact energy by 20%-30%). Vanadium lowers the critical cooling rate for phase transformation, allowing drill steel to achieve a more uniform bainitic-martensite multiphase structure under conventional quenching conditions, significantly improving tensile strength. Vanadium precipitates can alter the stress field at the crack tip, reducing the fatigue crack propagation rate (da / dN) by 30%-50%, extending the downhole service life of drill tools. Vanadium content is typically controlled between 0.02% and 0.20%; excessive vanadium (>0.3%) easily forms coarse carbides, leading to decreased toughness. This invention defines the V content range as 0.02%-0.20%.

[0046] 8) Determination of W content

[0047] Tungsten (W) improves the tempering resistance of steel, and its carbides are very hard, thus improving the wear resistance of the steel and giving it a certain degree of hot hardness. It also enhances the creep resistance of the steel at high temperatures. During quenching, carbides such as (FeW6)C are difficult to dissolve, thus refining the grain size. In the tempering process, within the temperature range of 500–600℃, tungsten carbides, primarily W2C, precipitate and disperse in the martensitic matrix, providing secondary hardening. However, due to the high melting point of W, and to minimize stress concentration caused by tungsten inclusions while ensuring high-temperature strength, and considering smelting cost control, the W content in this invention is determined to be in the range of 0.10–1.00%.

[0048] 9) Determination of Al content

[0049] Al is a deoxidizer in the smelting process. Besides reducing dissolved oxygen in molten steel, Al combines with N to form fine, dispersed aluminum nitride inclusions, which can refine the grain size. However, when the Al content exceeds 0.05%, the fluidity of the molten steel decreases significantly, increasing the difficulty of casting. In this invention, the Al content is defined as ≤0.05%.

[0050] 10) Determination of Ca content

[0051] Ca can form dot-like sulfides with S, altering the morphology of elongated sulfides and thus achieving excellent resistance to hydrogen sulfide. The optimal calcium-to-sulfur ratio is 2–2.5. However, excessive Ca content increases the number and size of dot-like oxides in the steel. Furthermore, because dot-like oxides have high hardness and poor plasticity, they do not deform during steel deformation and easily form voids at the interface, degrading the steel's properties. In this invention, the Ca content is determined to be in the range of 0.002–0.006%.

[0052] 11) Determination of Ti content

[0053] Ti detrimental to steel by remaining as titanium nitride and titanium carbonitride inclusions. These inclusions are hard and angular, severely affecting the fatigue life of the material, especially when the purity is significantly improved and the amount of other oxide inclusions is very small. In conjunction with smelting cost control, the Ti content range of this invention is determined to be ≤0.003%.

[0054] 12) Determination of O content

[0055] Oxygen content represents the total amount of oxide inclusions. The brittle inclusions of oxides significantly affect the service life of the finished product. Numerous experiments have shown that reducing oxygen content is significantly beneficial for improving steel purity, especially reducing the content of brittle oxide inclusions. This is also considered in conjunction with smelting cost control. Therefore, the oxygen content range in this invention is determined to be ≤0.0010%.

[0056] 13) Determination of P and S content

[0057] Phosphorus (P) in steel causes severe segregation during solidification. P dissolves in ferrite, leading to grain distortion and coarsening, and increasing cold brittleness. Considering both smelting cost control and other factors, the P content in this invention is determined to be ≤0.008%. Sulfur (S) causes hot brittleness in steel, reducing its ductility and toughness. S content in steel resistant to hydrogen sulfide corrosion needs strict control, also considering smelting cost control. Therefore, the S content in this invention is determined to be ≤0.002%.

[0058] 14) Determination of the contents of As, Sn, Sb and Pb

[0059] Trace elements such as As, Sn, Sb, and Pb are all low-melting-point non-ferrous metals. Their presence in steel causes soft spots and uneven hardness on the surface of parts. Therefore, they are considered harmful elements in steel, and this is also considered in conjunction with smelting cost control. The content range of these elements in this invention is defined as As ≤ 0.04%, Sn ≤ 0.03%, Sb ≤ 0.005%, and Pb ≤ 0.002%.

[0060] 15) Determination of Pd content

[0061] Palladium is a highly efficient "hydrogen trap" element with excellent hydrogen absorption and storage capabilities. Its crystal lattice can adsorb and dissolve diffusible hydrogen atoms, reducing their migration and diffusion within the steel by pinning them, thus preventing the formation and propagation of hydrogen embrittlement cracks. However, as a precious metal, palladium is relatively expensive, necessitating cost control in smelting. Therefore, the Pd content in this invention is determined to be in the range of 0.01–0.02%.

[0062] 16) Determination of La content

[0063] Lanthanum, as a rare earth element, has a high affinity for both oxygen and sulfur. It can react with residual oxygen and sulfur in steel to form rare earth oxide and rare earth sulfide inclusions. La-based inclusions not only reduce the induction of fatigue cracks by large inclusions but also adsorb some diffusible hydrogen, further reducing the destructive effect of hydrogen on the matrix. Excessive La may form coarse rare earth oxide inclusions, becoming new crack sources and thus reducing the overall performance of the steel. In this invention, the La content is determined to be in the range of 0.005~0.015%.

[0064] The requirements for non-metallic inclusions in the bars of this invention are shown in Table 1 below:

[0065] Table 1 Requirements for Non-metallic Inclusions

[0066]

[0067] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) By introducing palladium, a highly efficient hydrogen trap is formed in the steel matrix, reducing the concentration and migration rate of diffusing hydrogen. Compared with the traditional technology, palladium can directly capture diffusing hydrogen atoms and prevent the enrichment of hydrogen and the initiation and propagation of cracks; (2) By introducing lanthanum, its high affinity with oxygen and sulfur in steel is used to generate La-based oxide / sulfide inclusions, turning sharp inclusions into spherical or diffusely distributed small-sized inclusions, reducing the nucleation source of fatigue cracks, and also adsorbing diffusing hydrogen, further reducing the harm of hydrogen. Detailed Implementation

[0068] The technical solution of the present invention will be described in detail below with reference to specific embodiments. The embodiments described herein are specific implementations of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limiting the implementation of the present invention or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of this application. These technical solutions include those that make any obvious substitutions and modifications to the embodiments described herein.

[0069] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone any further purification treatment.

[0070] Example 1

[0071] This embodiment provides high fatigue life alloy steel bars for oilfield drilling tools and their preparation method. The preparation method specifically includes the following steps:

[0072] S1, steel is fed into the electric arc furnace, the furnace temperature is maintained at 1600℃, and oxygen is blown in using an oxygen lance for 20 minutes at a flow rate of 300 Nm³.3 / h, lime and fluorite are added to form foam slag, the slag layer thickness is controlled at 10cm, molten steel is obtained, the molten steel is transferred to a vacuum induction melting furnace, vacuum is maintained and Pd wire and La wire are fed in sequence under argon atmosphere, the vacuum degree of the vacuum induction melting furnace is ≤0.08Pa, the feeding speed of the Pd wire is 10m / min, the diameter of the Pd wire is 1.0mm, the feeding speed of the La wire is 10m / min, the diameter of the La wire is 1.0mm, after the wire is fed, argon gas is gently blown for 15min, the argon gas flow rate is 13L / min, the crystallizer electromagnetic stirring is turned on, the current of the crystallizer electromagnetic stirring is 280A, the frequency is 2Hz, a light reduction process is implemented, the total reduction of the light reduction process is 4mm / m, and the continuous casting is obtained by casting, the casting temperature is 1530℃;

[0073] S2. The continuous casting is sequentially forged, rolled, normalized, and tempered. The initial forging temperature is 1150℃, the final forging temperature is 850℃, the total deformation is ≥4 times, and the single compression ratio is ≤30%. The initial rolling temperature is 1100℃, the final rolling temperature is 800℃, the reduction per rolling pass is ≤20%, and the rolling specification is Φ80mm. After rolling, the part is buried in sand for cooling. The normalizing temperature is 880℃, the heating rate is 10℃ / min, and the holding time is 90min. After exiting the furnace, it is air-cooled to room temperature. The tempering temperature is 540℃, the heating rate is 10℃ / min, and the holding time is 2h. After exiting the furnace, it is air-cooled to room temperature to obtain high fatigue life alloy steel bars for oilfield drilling tools.

[0074] Example 2

[0075] This embodiment provides high fatigue life alloy steel bars for oilfield drilling tools and their preparation method. The preparation method specifically includes the following steps:

[0076] S1, steel is fed into the electric arc furnace, the furnace temperature is maintained at 1620℃, and oxygen is blown in using an oxygen lance for 23 minutes at a flow rate of 330 Nm³. 3 / h, lime and fluorite are added to form foam slag, the slag layer thickness is controlled at 12cm, molten steel is obtained, the molten steel is transferred to a vacuum induction melting furnace, vacuum is maintained and Pd wire and La wire are fed in sequence under argon atmosphere, the vacuum degree of the vacuum induction melting furnace is ≤0.08Pa, the feeding speed of the Pd wire is 11m / min, the diameter of the Pd wire is 1.1mm, the feeding speed of the La wire is 12m / min, the diameter of the La wire is 1.2mm, after wire feeding, argon gas is gently blown for 17min, the argon gas flow rate is 14L / min, the electromagnetic stirring of the crystallizer is turned on, the current of the electromagnetic stirring of the crystallizer is 290A, the frequency is 2Hz, a light reduction process is implemented, the total reduction of the light reduction process is 4mm / m, and the continuous casting is obtained by casting, the casting temperature is 1560℃;

[0077] S2. The continuous casting is sequentially forged, rolled, normalized, and tempered. The initial forging temperature is 1200℃, the final forging temperature is 900℃, the total deformation is ≥4 times, and the single compression ratio is ≤30%. The initial rolling temperature is 1120℃, the final rolling temperature is 810℃, the reduction per rolling pass is ≤20%, and the rolling specification is Φ90mm. After rolling, the part is buried in sand for cooling. The normalizing temperature is 890℃, the heating rate is 15℃ / min, and the holding time is 93min. After exiting the furnace, it is air-cooled to room temperature. The tempering temperature is 550℃, the heating rate is 12℃ / min, and the holding time is 2.3h. After exiting the furnace, it is air-cooled to room temperature to obtain high fatigue life alloy steel bars for oilfield drilling tools.

[0078] Example 3

[0079] This embodiment provides high fatigue life alloy steel bars for oilfield drilling tools and their preparation method. The preparation method specifically includes the following steps:

[0080] S1, steel is fed into the electric arc furnace, the furnace temperature is maintained at 1650℃, and oxygen is blown in using an oxygen lance for 30 minutes at a flow rate of 400 Nm³. 3 / h, lime and fluorite are added to form foam slag, the slag layer thickness is controlled at 15cm, molten steel is obtained, the molten steel is transferred to a vacuum induction melting furnace, vacuum is maintained and Pd wire and La wire are fed in sequence under argon atmosphere, the vacuum degree of the vacuum induction melting furnace is ≤0.08Pa, the feeding speed of the Pd wire is 12m / min, the diameter of the Pd wire is 1.2mm, the feeding speed of the La wire is 11m / min, the diameter of the La wire is 1.0mm, after the wire is fed, argon gas is gently blown for 20min, the argon gas flow rate is 15L / min, the electromagnetic stirring of the crystallizer is turned on, the current of the electromagnetic stirring of the crystallizer is 300A, the frequency is 2Hz, a light reduction process is implemented, the total reduction of the light reduction process is 4mm / m, and the continuous casting is obtained by casting, the casting temperature is 1540℃;

[0081] S2. The continuous casting is sequentially forged, rolled, normalized, and tempered. The initial forging temperature is 1160℃, the final forging temperature is 860℃, the total deformation is ≥4 times, and the single compression ratio is ≤30%. The initial rolling temperature is 1150℃, the final rolling temperature is 850℃, the reduction per rolling pass is ≤20%, and the rolling specification is Φ100mm. After rolling, the part is buried in sand for cooling. The normalizing temperature is 900℃, the heating rate is 12℃ / min, and the holding time is 100min. After exiting the furnace, it is air-cooled to room temperature. The tempering temperature is 560℃, the heating rate is 15℃ / min, and the holding time is 3h. After exiting the furnace, it is air-cooled to room temperature to obtain high fatigue life alloy steel bars for oilfield drilling tools.

[0082] Example 4

[0083] This embodiment provides high fatigue life alloy steel bars for oilfield drilling tools and their preparation method. The preparation method specifically includes the following steps:

[0084] S1, steel is fed into the electric arc furnace, the furnace temperature is maintained at 1640℃, and oxygen is blown in using an oxygen lance for 27 minutes at a flow rate of 360 Nm³. 3 / h, lime and fluorite are added to form foam slag, the slag layer thickness is controlled at 11cm, molten steel is obtained, the molten steel is transferred to a vacuum induction melting furnace, vacuum is maintained and Pd wire and La wire are fed in sequence under argon atmosphere, the vacuum degree of the vacuum induction melting furnace is ≤0.08Pa, the feeding speed of the Pd wire is 10m / min, the diameter of the Pd wire is 1.0mm, the feeding speed of the La wire is 10m / min, the diameter of the La wire is 1.1mm, after the wire is fed, argon gas is gently blown for 18min, the argon gas flow rate is 13L / min, the crystallizer electromagnetic stirring is turned on, the current of the crystallizer electromagnetic stirring is 285A, the frequency is 2Hz, a light reduction process is implemented, the total reduction of the light reduction process is 4mm / m, and the continuous casting is obtained by casting, the casting temperature is 1550℃;

[0085] S2. The continuous casting is sequentially forged, rolled, normalized, and tempered. The initial forging temperature is 1180℃, the final forging temperature is 880℃, the total deformation is ≥4 times, and the single compression ratio is ≤30%. The initial rolling temperature is 1140℃, the final rolling temperature is 840℃, the reduction per rolling pass is ≤20%, and the rolling specification is Φ80mm. After rolling, the part is buried in sand for cooling. The normalizing temperature is 895℃, the heating rate is 14℃ / min, and the holding time is 97min. After exiting the furnace, it is air-cooled to room temperature. The tempering temperature is 545℃, the heating rate is 14℃ / min, and the holding time is 2.7h. After exiting the furnace, it is air-cooled to room temperature to obtain high fatigue life alloy steel bars for oilfield drilling tools.

[0086] Fatigue life testing method: The specimen is designed as an axisymmetric cylindrical rod with a smooth cylindrical working section. The specimen is ultrasonically cleaned with anhydrous ethanol or acetone to remove grease, oxides, and surface contaminants. Three specimens are set up for each test group (different stress amplitudes). Environmental simulation: The specimen is installed in a high-pressure reactor, and a high-pressure hydrogen environment (5 MPa) is set. The specimen is pretreated in the high-pressure hydrogen environment for 24 hours, and then in an electrolytic cell with the specimen as the cathode and high-purity graphite as the anode, the electrolyte solution is 0.1M H₂SO₄ solution, and a constant current density (2 mA / cm²) is controlled. 2 The sample was charged with hydrogen for 5 hours. After charging, the sample was removed, quickly cleaned, and dried. Experimental setup: A servo hydraulic fatigue testing machine was used, with a stress ratio R = -1. The loading frequency was controlled at 10 Hz to avoid thermal effects caused by high-frequency loading. The maximum number of loading cycles was set (10). 7 (After one time), a specimen that does not break is considered to have reached the fatigue limit.

[0087] The chemical composition (wt%) of Examples 1-4 and 4330V steel is shown in Tables 2 and 3.

[0088] Examples 1-4 and the non-metallic inclusions in 4330V steel are shown in Table 4.

[0089] Table 5 compares the fatigue life performance of Example 1 with that of 4330V steel.

[0090] Table 2 Chemical composition (wt%) of Examples 1-4 and 4330V steel

[0091]

[0092] Table 3 Chemical composition (wt%) of Examples 1-4 and 4330V steel

[0093]

[0094] Table 4 Non-metallic inclusions in Examples 1-4 and 4330V steel

[0095]

[0096] Table 5 Comparison of fatigue life performance between Example 1 and 4330V steel

[0097]

[0098] As shown in Tables 2, 3, and 4, the control levels of harmful elements such as oxygen, titanium, and non-metallic inclusions in the high fatigue life corrosion-resistant oilfield drilling tool rods of Examples 1-4 of this invention are superior to those of traditional 4330V steel. Table 5 shows that in fatigue life testing, the high fatigue life alloy steel rods prepared in Example 1, through the addition of palladium and lanthanum to achieve grain refinement, improved the material's fatigue resistance, effectively hindered the initiation and propagation of fatigue cracks, and delayed hydrogen diffusion in the material. Furthermore, the inclusion modification effect of lanthanum improved the inclusion characteristics in the material; lanthanum transformed sulfide inclusions into spherical or dispersed small particle inclusions, thereby reducing stress concentration effects and significantly reducing the possibility of crack initiation. Simultaneously, palladium effectively captured diffused hydrogen atoms, reducing the hydrogen concentration at the crack tip, thereby slowing the crack propagation rate and significantly inhibiting hydrogen embrittlement. In contrast, 4330V steel lacks a similar hydrogen trapping mechanism, leading to significant acceleration of crack propagation due to hydrogen enrichment at the crack tip, which is the main reason for its decreased fatigue life in a hydrogen environment.

[0099] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing high fatigue life alloy steel bars for oilfield drilling tools, characterized in that, The preparation method includes: S1. Steel is put into an electric arc furnace and oxygen is blown in with an oxygen lance. Lime and fluorite are added to form foam slag to obtain molten steel. The molten steel is transferred to a vacuum induction melting furnace, vacuum is drawn and maintained, and Pd wire and La wire are fed in sequence under argon atmosphere. After feeding the wire, argon is blown in soft air, the crystallizer is turned on with electromagnetic stirring, and a light pressing process is implemented to cast the continuous casting. S2, the continuous casting is forged, rolled, normalized and tempered in sequence to obtain high fatigue life alloy steel bars for oilfield drilling tools; The chemical composition of the high fatigue life alloy steel bar for oilfield drilling tools, by mass percentage, includes Pd: 0.01-0.02%, La: 0.005-0.015%, S: ≤0.002%, Ti: ≤0.003%, and O: ≤0.0010%.

2. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S1: The oxygen lance is used to blow oxygen for 20-30 minutes. The oxygen flow rate of the oxygen lance is 300-400 Nm. 3 / h; The vacuum degree of the vacuum induction melting furnace is ≤0.08Pa.

3. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S1: The feeding speed of the Pd wire is 10-12 m / min, and the diameter of the Pd wire is 1.0-1.2 mm; The feeding speed of the La filament is 10-12 m / min, and the diameter of the La filament is 1.0-1.2 mm.

4. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S1: The time for soft blowing of argon gas is ≥15 min, and the flow rate of argon gas is 13-15 L / min; The current of the electromagnetic stirring in the crystallizer is 280-300A, and the frequency is 2Hz.

5. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S1: The total reduction amount of the light reduction process is 4 mm / m; The pouring temperature is 1530-1560℃.

6. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S2: The initial forging temperature is 1150~1200℃, the final forging temperature is 850~900℃, the total deformation is ≥4 times, and the single compression ratio is ≤30%.

7. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S2: The initial rolling temperature is 1100~1150℃, the final rolling temperature is 800~850℃, the reduction per rolling pass is ≤20%, the rolling specification is Φ80-100mm, and the rolling is cooled by sand after rolling.

8. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S2: The normalizing temperature is 880-900℃, the heating rate is 10-15℃ / min, the holding time is 90-100min, and after being taken out of the furnace, it is air-cooled to room temperature.

9. The method for preparing high fatigue life alloy steel bars for oilfield drilling tools according to claim 1, characterized in that, In S2: The tempering temperature is 540-560℃, the heating rate is 10-15℃ / min, the holding time is 2-3h, and after being taken out of the furnace, it is air-cooled to room temperature.

10. A high fatigue life alloy steel bar for oilfield drilling tools prepared by the preparation method according to any one of claims 1-9, characterized in that, The chemical composition content, expressed as a percentage by mass, is as follows: C: 0.20–0.75%, Si: 0.10–0.60%, Mn: 0.10–0.85%, Cr: 0.80–1.90%, Pd: 0.01–0.02%, La: 0.005–0.015%, S: ≤0.002%, P≤0.008%, Nb: 0.01–0.08%, Mo: 0.10–0.80%, V: 0.02–0.20%, W: 0.10–1.00%, Al≤0.05%, Ca: 0.002–0.006%, Ti≤0.003%, O≤0.0010%, As≤0.04%, Sn≤0.03%, Sb≤0.005%, Pb≤0.002%, balance Fe.